Perencanaan Strategis Sistem Informasi Menggunakan Metode Tozer - Nurhayati, Nurhayati; Purnasari, Manja; Karman, Zulfi; Hartiwi, Yessi (TIN: Terapan Informatika Nusantara, 2025)
This study aims to design a strategic information system plan for the Nipah Panjang Sub-District Office using the TOZER method. The main problem identified is the absence of an integrated information system, which results in data duplication and difficulties in managing public service data. The TOZER methodology is employed to analyze the strategic needs of the information system through five phases: defining the scope and context, identifying business information and support needs, evaluating the existing systems, formulating strategic solutions, and planning for implementation. The analysis produced an information system portfolio that includes proposed applications such as the Public Service Information System (SIPMAS), Public Complaints Information System (SIDUMAS), Personnel Information System (SIKEP), and a web-based information system. This strategy is expected to enhance the efficiency and effectiveness of public services.